The Investigation of Factors Affecting the purchasing decisions of consumers of green products - Jouzdani, Maryam (2020)
Goal: The purpose of this study was to investigate the factors affecting the purchasing decisions of consumers of green products.  Design / Methodology / Approach: The sample of this study was composed of consumers of disposable products in Isfahan. In this study, Descriptive statistics is used for data analysis and Structural Equation Modeling is used test the research hypotheses and determine the effect of independent variables on the dependent variable. Results: Considering the critical values obtained from the research hypothesis test, it can be concluded that environmental protection, environmental responsibility, green product experience, environmentally friendly brands and social acceptance have a positive and significant effect on green product purchase decisions. Limitations of the investigation: Since the present study is an exploratory study, the findings of the study are limited to the sample and results may be changed if the sample is changed. Also, the sample of green product buyers' decisions was obtained from only one province, so the results may not be generalizable to all provinces of Iran. Practical Implications: According to the results, it is recommended that environment-friendly companies differentiate their products from other products and price them appropriately. This should have an impact on consumers and encourage them to buy and use green products. Originality / Value: The design of the products in a recyclable form and making their components and materials reusable will in future cause their raw materials are recycled and reused; thus, buyers are more eager to buy green products with regard to environmental protection.